Условия и факторы эффективной деятельности аграрных предприятий - Митяй, О.В. (Культура народов Причерноморья, 2013)
В статье раскрыты особенности аграрной отрасли, которые заключаются в наращивание объемов производства и реализации сельскохозяйственной продукции при соблюдении как технологических, так и экономических, предпосылок обеспечения процесса производства. Основной предпосылкой обеспечения бесперебойности процесса производства является получение прибыли, благодаря которому средства планомерно функционируют на всех стадиях круговорота. В статті розкрито особливості аграрної галузі, які полягають в нарощування обсягів виробництва та реалізації сільськогосподарської продукції при дотриманні як технологічних, так і економічних передумов забезпечення процесу виробництва. Основною передумовою забезпечення безперебійності процесу виробництва є отримання прибутку, завдяки якому кошти планомірно функціонують на всіх стадіях кругообігу The features of agricultural industry, which are in the increase of production and distribution of agricultural products subject to both technological and economic conditions of maintaining production process, are depicted in the article. The main condition of maintaining production process is getting profit, due to which the work of an enterprise is regularly supported at all stages. Thus, the way of improving an agricultural enterprise management is to develop the methods and techniques of operation management, including: democratization of the entire system of organization and economic relation; combining economic and administrative methods of regulating subdivisions activity and separate workers; a contract system of employment and payment which encourages the responsibility for the results of the work at all stages – from a director to a worker.